Canine soft tissue sarcomas: the expression of RUNX2 and karyopherin alpha-2 in extraskeletal (soft tissues) and skeletal osteosarcomas - Leonardi, Leonardo; Manuali, Elisabetta; Bufalari, Antonello; Porcellato, Ilaria (Frontiers in Veterinary Science, 2024)
As well described by the WHO classification of tumors of soft tissue and bone, Extraskeletal Osteosarcomas (EOS) are malignant neoplasia composed of neoplastic cells producing bone matrix, as is the case for primary osteosarcomas of the bone (POS). In humans and animals’ epidemiology data reports that EOSs arise in the deep soft tissues other than bones without primary involvement of the skeletal system. Usually, EOSs arising and grow as highly infiltrating, very rapidly growing masses containing areas of ossification at different levels of maturation, often mixed with areas of necrosis and hemorrhages. Some cases described in the literature report primitive onset of these tumors after the application of therapeutic protocols after exposure to radiation, while other etiopathogenetic hypotheses refer to cases developed de novo or which can arise from metaplastic bone foci, of which the most described are represented by those of EOS of the breast. EOS has histological features similar with POS, with high metastatic frequency. The aim of our work is to try to describe in a comparative way between EOS and POS the most significant morphological and immunohistochemical differences correlated to the degree of formation of the bone matrix and the diffusion/invasion characters of the tissues involved.